Atención al cliente del local comercial “La Magia Del Color" en el cantón Ventanas del periodo 2023. - Ulloa Navarro, Samanta Yaleli (2025)
This study analyzes customer service in the La Magia del Color commercial premises in the Ventanas canton during the 2023 period, with the aim of identifying the main deficiencies in the service and proposing improvement strategies that contribute to customer satisfaction and business growth. Through customer surveys and staff interviews, issues related to lack of customer service training, long wait times, and poor communication about products and promotions were identified. The results show that, although customers value the quality of the products and the variety of items available, the lack of an efficient service limits loyalty and reduces the competitiveness of the business in the local market. In this sense, it is concluded that the optimization of customer service is a key factor to improve business performance. The implementation of training, the use of technological tools and a more efficient communication strategy will contribute to strengthening the relationship with customers, increasing their satisfaction and consolidating the presence of the store in the market. It is recommended that Magia del Color implement a continuous training program for its staff, in order to improve the quality of service. In addition, the incorporation of digital tools such as information channels on social networks and instant messaging is suggested, which would optimize communication with customers and generate a more satisfactory shopping experience. These improvements will promote consumer loyalty and strengthen the competitiveness of the business in the sector.